Análisis del efecto del tratamiento magnético sobre la actividad enzimática en semillas de maíz (Zea mays L.) (2019)
The development of a plant starts in germination, determined by various processes such as water absorption and adsorption, gene replication and expression, hormonal and enzymatic activity, among others. These processes have been studied, seeking sensitivity, directly or indirectly to the magnetic treatment of seeds, however it is still necessary to investigate the modified processes in biological, biochemical and biophysical variables. This is why corn seeds were exposed to a magnetic flux density of 100 mT, times between 55 s and 543 s and water volumes between 12.2 mL and 23.8 mL. In the first instance, germination parameter responses were evaluated (maximum germination percentage, germination time of 50 % of seeds (t50) and times t1, t10, t25, t75 and t90) and enzymatic activity by spectrophotometry of both alpha amylase and proteases, at a wavelength of 500 nm and 660 nm respectively. To advance the understanding of the processes modified by the action of the magnetic treatment (MT) of corn seeds, the germination parameters were correlated with the enzymatic activity. The effect of MT is mainly reported in t50 and Gmax, obtaining reductions up to 31 % in t50 and increase of 16 % in Gmax. Enzyme activity increased in alpha amylases and proteases up to 68 % and 85.81 %, respectively. The correlation of the alpha amylases activity with the germination variables was direct with Gmax and inverse in t50, in proteases an inverse correlation with t50 was found. It is concluded that the magnetic treatment in corn seeds directly affects germination and increases the enzymatic activity of alpha amylases and proteases. The obtained results allow to contribute to the understanding of the processes modified by the MT action in corn seeds and consequently on the mobilization of reserve substances. At a biotechnological level, the MT makes it possible to optimize the germination process in an environmentally reliable, affordable and low cost; also the use of the MT can be considered as a useful tool to improve the performance of the processes where hydrolytic enzymes act.